Non-Intrusive Electrodynamic Characteristic Measurement for Circular Shape Electrode - Mohd Riduwan, Ghazali; Wan Ismail, Ibrahim; M.F, Rahmat (2011)
Abstract—The electrostatic sensor was used in process industry because of low cost and robust designed.Three types of electrode available in particular application such as pin shape, quarter ring shape and ring shape. The paper was focused on the investigation of the pin shape structure and the characteristic of the circular shape by using different size of structure. Non-instrusive method with circular electrode will be designed and applied to the shape.The sensitivity and spatial filtering effect of sensor will be investigated by using different size of electrodes.Then, the model will be proposed and compared with experimental result.